A Premature Termination Mutation in a Patient with Lowe Syndrome without Congenital Cataracts: Dropping the “O” in OCRL - Pasternack, S. M.; Böckenhauer, D.; Refke, M.; Tasic, V.; Draaken, M.; Conrad, C.; Born, M.; Betz, R. C.; Reutter, H.; Ludwig, M. (Klinische Pädiatrie, 2013)
The oculocerebrorenal syndrome of Lowe is an X-linked recessive disorder characterized by the triad of congenital cataracts, mental retardation and a renal proximal tubulopathy. Although severity of phenotype might vary, congenital cataracts are part of the definition of this rare disorder.We report a 13-year-old patient with the typical cerebrorenal phenotype of Lowe syndrome, that had remained undiagnosed due to absence of any ocular involvement. OCRL gene analysis was carried.DNA analysis revealed a c.C760T (p.Gln199X) nonsense mutation in exon 8 expected to cause complete disruption of OCRL function. After sequencing the parents of the index patient and his maternal grandparents, this mutation turned out to be de novo in the mother. Furthermore, a silent variant (p.Arg35=) was identified in exon 2, that could also be identified in the mother and her 3 sisters, but not in the grandparents assuming germ cell mosaicism in either of the grandparents. RNA analysis from the patient’s lymphocytes revealed presence of full-length OCRL transcripts. Western blotting from lymphocyte samples failed to detect OCRL protein even in controls.Our findings extend the phenotypic spectrum caused by OCRL mutations and illustrate that there may be selective organ involvement in Lowe syndrome.
Keywords: Lowe syndrome; congenital cataracts; OCRL gene; RNA analysis; translation reinitiation; alternative start codon